Century-Long Cycles of Evolution of the Country’s Active Population - A. I. Latysheva (Статистика и экономика, 2025)
The article investigates the issues of cyclical evolution of the country’s active population, using the example of the zemstvo statistics of the Perm region. The collected factual material allows us to draw a conclusion about the general patterns of creative activity of the population both at the beginning of the last century and in our years. The state program allows statistical services to analyze the economically active population with the greatest efficiency and make recommendations on the socio-economic development of the region. The scientific paper provides economically sound recommendations and suggestions for measures for the rational use of active population in the digital period of the country’s development.Purpose and methodology of the research. This article aims to provide an overall picture of the evolution of the country’s active population, identify factors of change, general principles and offer recommendations for solving some problems of the population. The study was conducted using a systematic approach.Results of research and discussion. The term “active population” was first used in the pre-revolutionary census of 1897. During this time, it has undergone multiple changes and the population itself has evolved. Free land for the enterprising active population has always been attractive. Their gaze, since the times of explorers, has always been directed to the “land-rich East”. By the end of the XIX century, the “center of gravity” of the population boldly stepped beyond the Urals and stopped near Novosibirsk. The driver of this flow was, in our opinion, the “active population”.In statistical surveys the term “active population” means – all persons who have an independent source of livelihood, regardless of its type [4]. In the future, when conducting censuses, the active population was obtained by calculation. Almost always there was not exhaustive data for inclusion in the calculations of the active population, but it was impossible to ignore them. Even the very fact as the growth of employment of the population due to personal entrepreneurship was impressive. The Central Statistical Committee of tsarist times counted the active population according to its actual existence. Later, in the period of wars and revolutions, uncontrolled movement of refugees and prisoners and unpredictability of death and birth rates, any statistical surveys became dark and guessing.With such quality of statistical material, it was impossible to fully vouch for the error-free nature of all subsequent constructions. However, the results based on the census are quite reliable reference points for the study of the evolution of the country’s active population. Though one has to spend a lot of wit and labor to create at least an approximate picture.